Self and Stuff: Accumulation in Francophone Literature and Art - Natalie Edwards; Amy L Hubbell (Studies in 20th & 21st Century Literature, 2014)
Introduction.
Keywords: accumulation; Francophone literature; autobiography; fiction; trauma; community